Determining the direction of the water flow near the village of Kokpekty using the GOOGLEEARTH program - Kurmankina D. T Курманкина Д. Т; Karzhauova S.A. Каржауова С.А (Рroblems of engineering and professional education, 2023)
The program GoogleEarth - project of Google, in which the Internet were placed satellite images of the Earth’s surface. Photos of some regions have an unprecedented high resolution. The program has many features to get more information about a specific area. In our case - the construction of the terrain profile.